Improved health outcomes of nasopharyngeal carcinoma patients 3 years after treatment by the AI-assisted home enteral nutrition management - Jia Liu; Xiuying Wang; Xu Ye; Danna Chen (Frontiers in Nutrition)
ObjectivesPatients with nasopharyngeal carcinoma (NPC) are prone to malnutrition, which leads to deterioration of health. This study is to clarify the effect of Artificial intelligence (AI)-assisted home enteral nutrition (HEN) management mode on the health status of patients with stage III to stage IV NPC after 3 years of treatment, and to provide a new strategy for improving the quality of life of patients.MethodsPatients with stage III ~ IV NPC were determined whether to accept AI-assisted HEN management according to voluntary principle. After 3 years of management, the survival rate, distant metastasis rate and local recurrence rate were counted, and the basic body quality, laboratory detection, eating difficulty score, mental health score and other examinations were performed on the surviving patients to evaluate the overall health status.ResultsThe three-year survival rate of patients with NPC who received AI-assisted HEN management after treatment was improved. Various tests showed that AI-assisted HEN improved the nutritional intake of patients, had a low positive rate of Epstein–Barr virus, reduced adverse reactions such as psychological stress and physical pain, and could improve the quality of life of patients.ConclusionAI-assisted HEN has a positive auxiliary effect on clinical treatment, which is helpful to promote the recovery of patients with NPC.Clinical trial registrationNCT06603909.